Sustainable community engagement within the Arts: A conceptual framework - Brand, Yvonne-Marié; Morelli, Janelize (Critical Studies in Teaching and Learning, 2025)
This conceptual paper explores the complexities of fostering sustainable community engagement within the Arts by developing a theoretically grounded framework informed by the literature and practice. Our engagement with the topic emerged through an iterative process of critical reflection and qualitative document analysis. Rather than offering prescriptive models or fixed outcomes, we present this framework as a contribution to the ongoing dialogue about the role of the Arts in higher education contexts in advancing sustainability. We begin by positioning our work within current debates on community engagement and sustainability, followed by a discussion of the theoretical framing that guided the conceptual development of our argument. The framework is structured on the basis of six interrelated themes – culturally responsive practices, integrated cross-disciplinary collaboration, dynamic impact assessment, synergistic community alliances, systems integration, and reflective practice. We offer these as entry points for further reflection and refinement, particularly for scholars and practitioners navigating the intersection of the Arts, education and sustainable community engagement